ANALISIS DAMPAK PROGRAM PENANGGULANGAN KEMISKINAN TERHADAP KEMISKINAN KECAMATAN STUDI DI KABUPATEN SLEMAN PADA TAHUN 2008-2012 - , Kharis Fadlan Borni ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The economic crisis of 1997/1998 provokes national consciousness that many people are vulnerable to poverty in Indonesia. To solve the problems of poverty, Indonesian government has issued many programs and strategy to tackle it. Here, the budgeting becomes one of the important resources for tackling poverty. One of the developed national programs on poverty alleviation-oriented is the program of Social Direct Aid (Bantuan Langsung Masyarakat/BLM), Rural and Urban National Program for Human Empowerment Mandiri (Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan dan Perkotaan/ PNPM). For local/rural policy, government also issues Village Fund Allocation (Alokasi Dana Desa/ADD). Year to year, both of these programs increasingly allocate a big enough budget of its trend. Sleman Regency is one of regencies in Indonesia developing both policies on poverty alleviation program. The interesting fact to question is why much money has been provided by the government to support the poverty reduction program, but it does not significantly reduce the level of poverty. This study seeks to determine the trends of poverty, the location of poverty and the impacts of budgetary on poverty reduction programs towards the level of districtâs poverty in Sleman. Using panel data from 2008-2012, the trend analysis tool, Klassen typology and Pooled Least Squares (PLS), the study finds that 1) the trend of poverty in Sleman tends to rise, 2) poverty alleviation programs do not effectively reduce poverty and,3) BLMPNPM does not significantly affect the level of districtâs poverty, while ADD significantly affects it.